A hundred heart failure deaths: lessons learnt from the Dr Foster heart failure hospital mortality alert. Issue 1 (30th March 2019) - Tran, Patrick; McDonald, Michelle; Kunaselan, Lleika; Umar, Fraz; Banerjee, Prithwish
Abstract : Background: Despite advances in evidence-based pharmacotherapy, the latest National Heart Failure Audit (NHFA) has shown that in-hospital mortality of heart failure (HF) remains high with large interhospital variations. University Hospitals Coventry & Warwickshire, a tertiary cardiac centre, received a mortality alert of excess HF deaths based on a high Dr Foster hospital standardised mortality ratio (HSMR). This conflicted with our local NHFA data which showed lower than national average mortality rates. Objective: To review various systemic and individual processes of care in patients admitted with HF and examine the validity of HSMR in HF. Design, setting, patients: A retrospective case note analysis was performed on a random sample of 100 HF deaths identified by Dr Foster from 2010 to 2016. Measures: Case record reviews were performed on the following aspects of care: admission to appropriate wards, resuscitation status, palliative care input and National Confidential Enquiry into Patient Outcome and Death classification. Primary diagnosis coding, diagnostic accuracy and actual causes of death were examined to assess limitations of HSMR. Results: Despite evidence of lower mortality on cardiology wards, only 28% of patients with acute HF were admitted to a cardiology-ward. Sixty four per cent were considered palliative but only 4.6% were referred to palliative care. The Do Not Attempt Resuscitation order was appropriate in 91% patients but only 74% had this in place. The primary diagnosis of HF was incorrectly coded in 34% while three cases were misdiagnosed. Conclusion: HF may be coded as a cause of death in some cases where the cause is uncertain and misdiagnosed. Although HSMR has many limitations, it is a smoke alarm that should not be ignored.